Melatonin reduces excitotoxic blood–brain barrier breakdown in neonatal rats. (17th December 2015) - Moretti, R.; Zanin, A.; Pansiot, J.; Spiri, D.; Manganozzi, L.; Kratzer, I.; Favero, G.; Vasiljevic, A.; Rinaldi, V.E.; Pic, I.; Massano, D.; D'Agostino, I.; et al.
Highlights: Using a model of neonatal excitotoxic brain injury, we shows an early opening of the BBB that likely contributes to damage. In this model, we demonstrate that melatonin specifically prevents this early BBB alteration. Our study shows an early BBB disruption in perinatal damage and further extend the neuroprotective profile of melatonin. Abstract: The blood–brain barrier (BBB) is a complex structure that protects the central nervous system from peripheral insults. Understanding the molecular basis of BBB function and dysfunction holds significant potential for future strategies to prevent and treat neurological damage. The aim of our study was (1) to investigate BBB alterations following excitotoxicity and (2) to test the protective properties of melatonin. Ibotenate, a glutamate analog, was injected intracerebrally in postnatal day 5 (P5) rat pups to mimic excitotoxic injury. Animals were than randomly divided into two groups, one receiving intraperitoneal (i.p.) melatonin injections (5 mg/kg), and the other phosphate buffer saline (PBS) injections. Pups were sacrificed 2, 4 and 18 h after ibotenate injection. We determined lesion size at 5 days by histology, the location and organization of tight junction (TJ) proteins by immunohistochemical studies, and BBB leakage by dextran extravasation. Expression levels of BBB genes (TJs, efflux transporters and detoxification enzymes) were determined in the cortex and choroid plexus by quantitative PCR. Dextran extravasation was seen 2 h after the insult, suggesting a rapid BBB breakdown that was resolved by 4 h. Extravasation was significantly reduced in melatonin-treated pups. Gene expression and immunohistochemical assays showed dynamic BBB modifications during the first 4 h, partially prevented by melatonin. Lesion-size measurements confirmed white matter neuroprotection by melatonin. Our study is the first to evaluate BBB structure and function at a very early time point following excitotoxicity in neonates. Melatonin neuroprotects by preventing TJ modifications and BBB disruption at this early phase, before its previously demonstrated anti-inflammatory, antioxidant and axonal regrowth-promoting effects.